Analisis Dan Perancangan E-CRM Wakagangga Menggunakan Metode Framework Of Dynamic CRM - Chandra Wulandari; Ni Made Estiyanti; I Nyoman Yudi Anggara Wijaya (Primakara University, 2021)
In terms of data processing and decision making for an agency, institution or business entity requires a lot of consideration. In the field of tourism, making decisions to be able to attract tourists requires various data, for example the small amount of consumer bio data and the things they like. Hospitality is one of the attributes in tourism that also requires processing of consumer data so that it can help hotels get more and of course loyal customers. ECRM is the right method in terms of processing this data, so that the hotel can be better.